Back Extensor Endurance: A Comparison Between Normal Healthy Indian Adults - Bhaval, Rashmi; Anap, Deepak; Rao, Keerthi; Iyer, Chandra; Khatri, S.M. (Asian Journal of Biological and Life Sciences, 2012)
The spinal muscles are the main proportion of human musculature and foundation of correct posture and are a huge group. Basically, back extensors play an important role in prevention and treatment of low back pain and are proven clinically with more credit to its endurance as compared to its strength. Thus, this study was done to assess the endurance of back extensors in normal individuals. Experimental study using simple random sampling. In this study Sorensen's test was assessed in twenty normal individuals. After applying t-pearson's test it was found that females (61.8±7.997) have higher back endurance than males (44.7±11.945). The study concluded that average values obtained in all the tests are higher in females as compared to males in the population under study.